Turnout among non-western immigrants - Bhatti, Yosef; Hansen, Kasper Møller (Politica, 2017)
Electoral turnout among non-western immigrants is substantially lower than among ethnic Danes. How much of the difference in turnout is simply due to different demographic compositions of the two groups? In the 2013 Danish municipal election, first-generation non-western immigrants voted 31 percentage points less than ethnic Danes, even when demographic composition is taken into consideration. Second-generation non-western immigrants voted 4 percentage points less than the first generation when demographic composition is not considered, but 7 percentage points more under control for the two groups’ different demographic composition. The gap in turnout between second-generation non-western immigrants and ethnic Danes shrinks when demographic composition is considered, but the group still lags 24 percentage points behind. Danish citizens turn out more than non-Danish citizens, but we do not find strong evidence of an effect of becoming a citizen when we try to identify the independent effect of this factor. The analysis indicates that the process up to becoming a citizen increases turnout at the municipal election, but that this effect disappears when citizenship is obtained. However, there is a need for more studies in the area.